2020 News & Views: Global warming changes the forecast for agriculture - International Food Policy Research Institute (International Food Policy Research Institute, 2001)
The latest predictions show that the earth's climate is changing faster than previously thought. How can agriculture remain productive in a warmer world while doing its part to slow climate change?